PD-1+ CD4 T cell immune response is mediated by HIF-1α/NFATc1 pathway after P. yoelii infection - Wei, Haixia; Xie, Anqi; Li, Jiajie; Fang, Chao; Liu, Lin; Xing, Junmin; Shi, Feihu; Mo, Feng; Chen, Dianhui; Xie, Hongyan; Yang, Quan; Pan, Xingfei; et al. (Frontiers in Immunology, 2022)
The morbidity and mortality of malaria are still high. Programmed cell death-1(PD-1) is an important co-inhibitory factor and CD8 T cells with PD-1 were reported to be exhausted cells. It remains unknown what the role of CD4 T cells expressing PD-1 is and what the upstream regulating molecules of PD-1 in CD4 T cells are. The C57BL/6 mice were injected with Plasmodium yoelii (P. yoelii) in this study. Expressions of PD-1, activation markers, and cytokines were tested. The differentially expressed genes between PD-1+/- CD4 T cells were detected by microarray sequencing. Western blot, chromatin immunoprecipitation (ChIP), siRNA, hypoxia inducible factor-1α (HIF-1α) inducer and inhibitor were used to explore PD-1’s upstream molecules, respectively. The proportions of PD-1+ CD4 T cells increased post P. yoelii infection. PD-1+ CD4 T cells expressed more activated surface markers and could produce more cytokines. Nuclear factor of activated T cells 1 (NFATc1) was found to be a key transcription factor to induce PD-1 expression after infection. Both the inducer and the inhibitor of HIF-1α could change the expressions of NFATc1 and PD-1 in vivo and in vitro, respectively. Taken together, P. yoelii infection induced NFATc1 expression by HIF-1α. The highly expressed NFATc1 entered the nucleus and initiated PD-1 expression. PD-1+ CD4 T cells appeared to be more activated and could secrete more cytokines to regulate the host’s immune responses against malaria.